REPRESENTASI MAKNA SINTAGMATIK DAN PARADIGMATIK DALAM NOVEL CA BAU KAN KARYA REMY SILADO: ANALISIS SEMIOTIKA STRUKTURAL - Herning Puspitarini; Sri Wahyuningtyas; Rusdian Noor Dermawan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Ca Bau Kan is a novel that powerfully depicts history, Chinese culture, and the lives of women in colonial society. This novel is compelling because it presents social and cultural signs that can be analyzed through a semiotic approach. The methods used are the syntagmatic and paradigmatic approaches to semiotics to uncover representations of meaning. The research results reveal the following binary oppositions: 1) love and hate, 2) courage and fear, 3) victory and defeat, 4) freedom and colonization, and 5) the overarching ideological meaning that the characters continue to fight for their personal ideologies.